Implementation Of Multi Experts Multi Criteria Decision Making For Rehabilitation And Reconstruction Action After A Disaster - Wibowo Almais, Agung Teguh; Sarosa, Moechammad; Muslim, Muhammad Aziz (Department of Informatics Engineering, 2016)
Abstractâ€” This article is aimed to propose a method which used Non-Numeric assessment that is Multi Experts Multi Criteria Decision Making (MEMCDM) in order to construct supporting decision system in composing rehabilitation and reconstruction action after disaster. Because in all this time â€œPerencanaan dan Pengendalian Penanganan Bencana (P3B)â€ surveyor team does not have clear standard criteria to execute the compiling rehabilitation and reconstruction action after disaster. Method Multi Experts Multi Criteria Decision Making (MEMCDM) step is to determine the alternative, assessment scale, criteria, criteria quality, criteria quality negation, criteria aggregation, and the qualification expert score. In the stage of expert qualification score for primary and secondary data is different. In secondary data, the qualification score is based on the usage of expert amount. Meanwhile, for secondary data, the expert qualification score is based on the criteria amount which is chosen by the user. Training data that has been processed using method Multi Experts Multi Criteria Decision Making (MEMCDM) can form a pattern system to assess damage and losses after natural disasters. There for it could facilitate a team of surveyors in assessing the damage and losses after natural disasters.